Aedes albopictus may not be vector of dengue virus in human epidemics in Brazil Aedes albopictus pode não ser vetor da dengue durante epidemias no Brasil - Nicolas Degallier; José Marcus Sócrates Teixeira; Sidinei da Silva Soares; Regilene D Pereira; Santuzza C F Pinto; Antonio de Jesus Melo Chaib; Pedro F C Vasconcelos; Enilce Oliveira (Universidade de São Paulo, 2003)
Over 60,500 dengue cases were reported in the state of Espírito Santo (ES), Brazil, between 1995 and 1998. The study's purpose was to identify whether Aedes albopictus was transmitting the dengue virus during an epidemic in the locality of Vila Bethânia (Viana County),Vitória, ES. From April 3 to 9, 1998, blood and serum samples were collected daily for virus isolation and serological testing. Four autochthonous cases were confirmed through DEN 1 virus isolation and two autochthonous cases through MAC ELISA testing. Of 37 Ae. aegypti and 200 Ae. albopictus adult mosquitoes collected and inoculated, DEN1 virus was isolated only from a pool of two Ae. aegypti female mosquitoes. The study results suggest that Ae. albopictus still cannot be considered an inter-human vector in dengue epidemics in Brazil. Mais de 60.500 casos de dengue foram notificados no Espírito Santo, entre 1995 e 1998. Realizou-se estudo com o objetivo de averiguar se o mosquito Aedes albopictus estava transmitindo o vírus durante uma epidemia em Vila Bethânia (Viana), no sudeste de Vitória, capital capixaba. De 3 a 9 de abril de 1998, amostras de sangue e (ou) soro de pacientes foram coletadas e os mosquitos foram capturados diariamente, tanto para isolamento viral como para testes sorológicos. Em onze casos autóctonos, quatro foram confirmados por isolamento do vírus DEN 1, e dois por reação MAC ELISA Dos 37 Ae. aegypti e 200 Ae. albopictus adultos capturados e inoculados, apenas uma amostra de vírus DEN 1 foi obtida de um lote de duas fêmeas de Ae. aegypti. Os resultados sugerem que a espécie Ae. albopictus ainda não pode ser considerada um vetor inter-humano durante epidemias de dengue no Brasil.